Modal analysis of engine piston rod for small engine - Izzul Izwan, Ismail (2010)
In reciprocating small engine system, piston rod connects the piston and crankshafts. Piston rod is always under tremendous stress level created by load and force. It will produce great vibration. Sometimes the vibration is higher than the natural frequency of piston rod. This will lead to the piston rod failure in small engine. Situation which vibration frequency exceeding natural frequency is known as resonance. Finite element analysis and experimental modal analysis are two methods to investigate the dynamic behavior of piston rod and thus determining its natural frequency. Finite element analysis involved several mesh size. Result from both methods is compared and prominently discussed to achieve project objective. Finally, estimation of natural frequency and mesh size is suggested.